Efficacy of EMLA Cream in Pain Reduction during Botulinum Toxin Injections for Facial Dystonias - Abdullah Irfan, Muhammad Moin (Pakistan Journal of Ophthalmology, 2019)
Purpose: To determine the efficacy of EMLA cream (Eutectic Mixture of Local Anesthetics) in pain reduction while injecting botulinum toxin in patients with hemifacial spasm and blepharospasm. Study Design: Quasi Experimental Study. Place & Duration of Study: Yaqin Vision Eye center from January 2015 to December, 2018. Material & Methods: Patients undergoing routine treatment of Blepharospasm and Hemifacial spasm since 2010 were offered pre-injection EMLA cream application to reduce the pain during injections. A total of 74 Botulinum A toxin injections were given for blepharospam and hemifacial spasm, half of which were administered without the use of any topical analgesia while other half were given to same patient on next visit using EMLA cream 15 minutes prior to injection. Pain was assessed as mild, moderate and severe in all the patients by the consultant administering the medication. Results: Among 37 cases of facial dystonias, 17 (45.9%) were males and 20 (54.1%) were females. It was observed that when EMLA was not used, severe pain was observed during 8 injections (21.6%), moderate pain in 17 (45.9%), and mild pain in 12 (32.4%) sessions. However when EMLA was used mild pain was observed during 33 (89.2%) injections, moderate pain in 3 injections and severe pain in 1 (2.7%) case. There was a statistically significant difference in pain control during the sessions involving use of EMLA. Conclusion: Use of topical EMLA cream dramatically reduces the pain and makes the administration of botulinum toxin A injection easier in patients with hemifacial spasm and blepharospasm. Keywords: Topical anesthetia, Blepharospasm, Hemifacial spasm, Botulinum Toxin.